Transformasi Pembelajaran IPS melalui Pemanfaatan Teknologi Digital untuk Meningkatkan Minat Belajar Siswa SMP - Almadina Puspita Dewi; Desy Safitri; Sujarwo (PT. Penerbit Tiga Mutiara, 2025)
The shift in educational paradigms driven by advancements in digital technology has had a significant impact on Social Studies (IPS) learning at the Junior High School (SMP) level. This study aims to examine how digital technology can enhance student interest and engagement in IPS learning through a literature review approach. This study includes scientific articles published between 2023 and 2025 as primary references. The research findings indicate that the use of digital technology, such as flipped classroom models, interactive learning materials, and digital platforms, can encourage increased motivation and participation among students in IPS learning. However, the success of implementing this technology is highly influenced by several factors, including infrastructure readiness, teachers' competencies in integrating technology, and equitable access to technology. Adequate infrastructure readiness and teachers' ability to effectively utilize technology are key factors in creating engaging and meaningful learning experiences. Additionally, ensuring equitable access to technology for all students is crucial to ensure that every student can benefit from technology in learning. Based on these findings, this study recommends the development of continuous training programs for teachers to enhance their digital competencies and emphasizes the importance of implementing innovative teaching methods that can fully leverage the potential of technology. On the other hand, strengthening technology-based educational policies is also necessary to ensure that the implementation of technology in learning can be optimal and equitable. With the proper use of digital technology, IPS learning at the Junior High School level can become more engaging, interactive, and effective, thus supporting the overall improvement of education quality.